Social innovations as a repair of social order - Schubert, Cornelius (NOvation — Critical Studies of Innovation, 2019)
The paper addresses social innovation both as a mode and as a means of social change. It draws on the recent developments in the sociology of repair to offer a critical reading of pro-innovation discourse on the level of EU policy. It is argued that the practices and concepts of social innovation on the level of EU policy can be fruitfully reframed within a repair narrative, whereas the proliferation of the buzzword social innovation warrants a closer look from an innovation studies perspective. Connecting both repair and innovation studies thus offers a more nuanced understanding of current societal transformations and adds to the conceptual discussion of social change and social order.